Exchanging Bandwidth with Aperture Size in Wireless Indoor Localization - or why 5G/6G Systems with Antenna Arrays can Outperform UWB Solutions - Sippel, Erik; Geiß, Johanna; Brückner, Stefan; Gröschel, Patrick; Hehn, Markus; Vossiek, Martin (IEEE Open Journal of Vehicular Technology, 2021)
The localization of wireless devices in indoor scenarios presents a major challenge because of multipath propagation. Hence, the majority of the research community has focused on increasing the available bandwidth of localization systems, leading to the emergence of the ultra wide band (UWB) radar. However, the hardware implementation of UWB transceivers is challenging itself and, hence, their utilization in commercial low-cost wireless devices is not to be expected in the near future. Hence, instead of evaluating frequency dependent phases via UWB, the measurement of spatially distributed phases represents a valuable alternative. Therefore, this article presents a comparison of phase-difference-of-arrival (PDOA) and time-of-arrival (TOA) systems. For this purpose, we compare the measurement sensitivity, the effects of multipath propagation, and the hardware complexity. Based on the results, the applicability of typical position estimators is discussed. Thereby, we argue that PDOA-based localization with large receiver arrays appears to be the better choice to localize wireless devices, because it enables highly accurate positioning using narrow band signals without elaborated transmitter-receiver synchronization. To validate this, indoor localization measurements are presented and compared with UWB results in extant literatur